Composition dependence of structural and optical properties in epitaxial Sr(Sn1−xTix)O3 films. (5th February 2015) - Liu, Qinzhuang; Li, Bing; Li, Hong; Dai, Kai; Zhu, Guangping; Wang, Wei; Zhang, Yongxing; Gao, Guanyin; Dai, Jianming
Abstract: Epitaxial Sr(Sn1− x Ti x )O3 (SSTO, x = 0–1) thin films were grown on MgO substrates by a pulsed laser deposition technique. The effects of composition on the structural and optical properties of SSTO films were investigated. X-ray diffraction studies show that the lattice parameter decreases from 4.041 to 3.919 Å gradually with increasing Ti content from 0 to 1 in SSTO films. Optical spectra analysis reveals that the band gap energy E g decreases continuously from 4.44 to 3.78 eV over the entire doping range, which is explained by the decreasing degree of octahedral tilting distortion and thus the increasing tolerance factor caused by the increasing small-Ti-ion doping concentration.